Bioethics and moral decisions - Timbreza, Florentino T. (Quezon City, Philippines : C & E Publishing Inc., 2007)
...The central focus of this book, however, will be on the basic ethical principles of each theory, no matter how sketchy they may be. How they may applied to particular problems arising from a medical context will be specifically underscored in order to give the student some idea of the moral dilemmas that health care professionals usually encounter in medical practice... -- Preface
Chapter 1 Human existence and ethics -- Chapter 2 Ethical schools of thought (one) -- Chapter 3 Ethical schools of thought (two) -- Part two Moral issues (one) -- Natural of moral issue and moral reasoning -- Chapter 4 The Moral issue of abortion -- Chapter 5 The Moral issue of euthanasia -- Chapter 6 The Moral issue of suicide -- Chapter 7 The Moral issue of birth deformities -- Chapter 8 Redefinition and determination of death -- Chapter 9 The Moral issues of paternalism and truth-telling -- Chapter 10 The Moral issue of patient's rights -- Part three Moral issues (two) -- Chapter 11 The Moral issues of contraception and sterilization -- Chapter 12 The Moral issue of artificial insemination -- Chapter 13 The Moral issue of human experimentation -- Chapter 14 The Moral issue of genetic engineering -- Chapter 15 The Moral issues of behavior control and claim to health care -- Chapter 16 The Morality of human sexuality.
Includes bibliographical references and index.
Keywords: BIOETHICS